Tanggung Jawab Hukum Pengelola Wisata Air Umbul Ponggok terhadap Pengunjung Apabila Kecelakaan - Meka Aszuri Rahmayani; Arief Suryono (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
This research aims to explain the legal responsibility of Umbul Ponggok Water Tourism management whether it is in accordance with applicable procedures. This research uses descriptive empirical legal method with statute approach. Legal materials obtained from primary and secondary legal materials with literature research collection techniques, field studies with data analysis techniques using qualitative analysis techniques. The results of this study show that the manager fulfills his obligations in maintaining safety and protecting visitor rights. However, the research shows the importance of providing clearer information about insurance on tickets so that visitors understand their rights and obligations, and managers need to ensure safety standards are maintained to minimize future accidents. The legal responsibilities of tour operators include obligations towards the safety and protection of visitors. The manager has provided a SAR team, ambulance, and collaborated with referral hospitals. In addition, the manager has collaborated with PT Insurance Jasa Raharja Putea to provide insurance protection.